2015
DOI: 10.1155/2015/340828
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey on Porcine Cysticercosis in Nay Pyi Taw Area, Myanmar

Abstract: Cross-sectional surveys were conducted to determine the prevalence and associated risk factors of Taenia solium cysticercosis in pigs within Nay Pyi Taw area, Myanmar. Meat inspection in three slaughterhouses, ELISA test, and questionnaire surveys were conducted in this study. Three hundred pigs were inspected in slaughterhouses and 364 pigs were randomly selected and examined from 203 households from three townships in Nay Pyi Taw area. The prevalence of porcine cysticercosis in meat inspection was 23.67% (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
6
17
1
Order By: Relevance
“…(28) Consumption of raw or halfcooked T. solium larvae-containing pork is an indirect factor, since it causes taeniasis, which results in contamination of the environment with T.solium eggs, but causes cysticercosis upon autoinfection. This is supported by the study of Khaing et al (23) who reported that the risk factors of cysticercosis transmission are among others community cooking resulting in consumption of half-cooked or raw meat.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…(28) Consumption of raw or halfcooked T. solium larvae-containing pork is an indirect factor, since it causes taeniasis, which results in contamination of the environment with T.solium eggs, but causes cysticercosis upon autoinfection. This is supported by the study of Khaing et al (23) who reported that the risk factors of cysticercosis transmission are among others community cooking resulting in consumption of half-cooked or raw meat.…”
Section: Discussionsupporting
confidence: 54%
“…A study by Van De et al (22) in Vietnam reported that the sources of cysticercosis transmission are consumption of raw vegetables and fresh fruit, half-cooked pork, and unboiled drinking water. Unprotected river streams or water wells may become contaminated with T.solium eggs, (23) which can survive in water for long periods of time so becoming a source of cysticercosis transmission in pigs and humans. (1,5) Different results were obtained by Nkouawa et al (24) who reported that there was no significant relationship of the use of river water and vegetable consumption with cysticercosis.…”
Section: Discussionmentioning
confidence: 99%
“…In Myanmar, the prevalence of porcine cysticercosis in meat inspection was 23.67% (71/300) and base on antibody enzyme-linked immunosorbent assay (Ab-ELISA) survey in Nay Pyi Taw area, seroprevalence of T. solium cysticercosis in pigs was 15.93% (58/364) (Khaing et al, 2015). In addition, epidemiological survey showed that husbandry system, feed types for pig rearing and habits of farmer are main risk factors for porcine cysticercosis.…”
Section: Zoonotic Helminthiasismentioning
confidence: 99%
“…Cysticercosis, a ubiquitous disease of high economic and public health significance, is caused by Cysticercus cellulosae, the larval form of Taenia solium. It mainly affects the health and livelihood of subsistence farming communities in developing countries in Africa, Asia, and Latin America, where pigs are allowed to roam freely with free access to night soil (1). The disease is transmitted to humans by consumption of infective cysticerci in raw or undercooked pork or food and water contaminated with their eggs.…”
Section: Introductionmentioning
confidence: 99%